2000
DOI: 10.1093/arclin/15.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coaching on Detecting Feigned Cognitive Impairment with the Category Test

Abstract: In a replication and extension of previous research (Tenhula & Sweet, 1996), the current study investigated the utility of the Category Test (CT) for detecting feigned cognitive impairment. Ninety-two undergraduate participants were randomly assigned to one of three groups and administered the CT. A Coached Simulator group was instructed to simulate cognitive impairment and was provided test-taking strategies to avoid detection. An Uncoached Simulator group was simply instructed to feign impairment. A control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…On subtests I and II, the student controls made an average of less than 1 error, the brain-damaged group made an average of 1.2 errors, and the student malingering group made an average of 4.9 errors. These results are consistent with findings in the literature (e.g., Tenhula and Sweet, 1996;DiCarlo et al, 2000) suggesting that indeed, the HCT indexes perhaps most sensitive to malingering are errors on subtests I and II. However, it should be noted that participants in the current study were not coached as to HCT structure and content.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On subtests I and II, the student controls made an average of less than 1 error, the brain-damaged group made an average of 1.2 errors, and the student malingering group made an average of 4.9 errors. These results are consistent with findings in the literature (e.g., Tenhula and Sweet, 1996;DiCarlo et al, 2000) suggesting that indeed, the HCT indexes perhaps most sensitive to malingering are errors on subtests I and II. However, it should be noted that participants in the current study were not coached as to HCT structure and content.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to performance on subtests I and II, it has been suggested by several researchers that making more than one error on the first two subtests may be the single best predictor of malingering on the HCT, as even patients with severe brain injury rarely miss any of these items (e.g., DiCarlo et al, 2000;Tenhula & Sweet, 1996;Reitan & Wolfson, 1993). The current data are largely consistent with this suggestion but also indicate that a slightly greater percentage of errors are made on subtest II than subtest I and that a more liberal cut-off or two or more errors would misclassify substantially fewer individuals as malingering.…”
Section: Discussionmentioning
confidence: 99%
“…A cutoff of > 1 on Subtests I and II demonstrated the highest overall classification rate of 71% with 95% specificity and 49% sensitivity. This comparatively stronger performance of > 1 errors on Subtests I and II was consistent with previous studies by DiCarlo et al (2000), Forrest et al (2004), Tenhula and Sweet (1996), and Sweet and Nelson (2007). While an AUC of .72 signifies only acceptable discrimination (Hosmer & Lemeshow, 2000), a positive finding on this index resulted in a PPV of more than .90 at the expected base rate of exaggeration among this population (Ardolf et al, 2007).…”
supporting
confidence: 92%
“…The ''difficult items'' index was found to have the least effectiveness in the detection of malingering (Tenhula & Sweet). DiCarlo, Gfeller, and Oliveri (2000) conducted an extension and replication of Tenhula and Sweet's (1996) research. The study found malingering simulation groups scored lower than traumatic brain injury (TBI) and control groups.…”
Section: Introductionmentioning
confidence: 99%
“…The SPE was examined in four groups: normal controls (NC), symptom-coached simulators (SC), test-coached simulators (TC), and a group of unequivocal moderate to severe subacute traumatic brain injury patients (TBI). TC simulators have been shown to engage in more sophisticated malingering compared to SC simulators (DiCarlo, Gfeller, & Oliveri, 2000). The present investigation extends previous research on the SPE on the RAVLT (e.g., Bernard, 1991;Suhr, 2002;and Sullivan et al, 2002) by varying the coaching paradigm across sophisticated malingering groups, by using more stringent criteria to define suppression of the primacy effect (described above), and by investigating the diagnostic utility (i.e., documenting the classification accuracy statistics) of the SPE (i.e., suppression of the primacy effect) in predicting poor effort.…”
Section: Introductionmentioning
confidence: 99%